Gratitude-Based Hope Training Package Based on Islamic Sources and Evaluating Its Feasibility to Increase Life Satisfaction - Faezeh Tabrizian; mobin salehi; hamid rafieihonar (مطالعات اسلام و روانشناسی, 2020)
The purpose of the present study is to develop a gratitude-based hope training package based on Islamic sources and evaluating its feasibility to increase life satisfaction. The research approach was qualitative and quantitative and two methods of content analysis and experimental method were used. In the quantitative part data about gratitude and hope gathered from Islamic sources. The study population consisted of all single young girls aged 18-35 in the city of Qom with low socioeconomic status and three persons were selected using purposful sampling. The instrument used was Diener satisfaction with life scale. At first, gratitude-based hope training package was developed based on Islamic Hope Therapy Intervention by Salehi (2016) and by adding some gratitude techniques that were based on Islamic sources. Then experts were consulted to evaluate content validity and content validity index. Afterwards, the training package was conducted on participants using a single-subject multiple baseline design. Data were analyzed using graphs and visual analysis. The training package was approved by experts and its conduct feasibility was determined. Intervention also increased life satisfaction, which had stable progress and changes were maintained in a one-month follow-up. Therefore, Islamic gratitude-based hope training package can be used to increase the life satisfaction of young girls in deprived neighborhoods of Qom.